2018
DOI: 10.4236/ad.2018.62009
|View full text |Cite
|
Sign up to set email alerts
|

Construction Sequence of the Koh Ker Monuments Constrained by the Chemical Composition and Magnetic Susceptibility of Its Bricks

Abstract: Using a portable X-ray fluorescence analyzer and magnetic susceptibility meter, we measured fired bricks from nine temples (Prasat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…In other ancient Khmer monuments, such as Koh Ker, the analysis of the chemical composition of brick material provided valuable evidence for identifying the construction sequence [25], and the analysis of the chemical composition and magnetic susceptibility of laterite materials have aided in deducing the construction sequence of each building [26]. In addition, the sandstone study of Khmer monuments in Thailand successfully identified the provenance of the sandstone materials by chemical composition [27].…”
Section: Chemical Composition Analysismentioning
confidence: 99%
“…In other ancient Khmer monuments, such as Koh Ker, the analysis of the chemical composition of brick material provided valuable evidence for identifying the construction sequence [25], and the analysis of the chemical composition and magnetic susceptibility of laterite materials have aided in deducing the construction sequence of each building [26]. In addition, the sandstone study of Khmer monuments in Thailand successfully identified the provenance of the sandstone materials by chemical composition [27].…”
Section: Chemical Composition Analysismentioning
confidence: 99%
“…Information on how ancient brick was manufactured was reported in another study on the Bagan temples in Myanmar (Oh et al 2019) and a Cham Dynasty temple in Vietnam (Abdrakhimov and Abdrakhimova 2018). Furthermore, research in Cambodia employ analytical techniques to study the sequence of brick construction based on the changes in chemical composition from temples at Sambor Prei Kuk (Shimoda et al 2019) and Koh Ker (Uchida and Sakurai 2018). In Thailand, archaeological dating techniques such as thermoluminescence and optically stimulated luminescence were applied to bricks from archaeological sites at Wiang Kaen (Won-in et al 2008), Thung Tuk (Pailoplee et al 2010;Pailoplee et al 2016) and the brick wall at Songkhla (Puttagan et al 2019).…”
Section: Chemical Analysis Of Bricks In the Southeast Asian Regionmentioning
confidence: 99%